Hunting with Two Bullets: Moral Hazard with a Second Chance - Fagandini, Paulo (2018)
I study the moral hazard problem where an agent can create an extra instance of effort and potentially improve bad realizations of the outcome before the principal observes it. The agent cannot hide the outcome of his effort, but just the way he achieved it. Findings are that both, principal and agent, value the option of improving the outcome in case of a bad realization if doing so is cheap. I also find that contracted effort is not always decreasing in its cost. Finally, if the creation of the extra instance can cause a punishment for the principal, and if that punishment is sufficiently big, the principal will avoid writing contracts that incentive effort only on the extra chance.